Review article: the nutritional and pharmacological consequences of obesity surgery. Issue 6 (30th July 2014) - Stein, J.; Stier, C.; Raab, H.; Weiner, R.
Summary Background Obesity surgery is acknowledged as a highly effective therapy for morbidly obese patients. Beneficial short‐term effects on common comorbidities are practically undisputed, but a growing data pool from long‐term follow‐up reveals increasing evidence of potentially severe nutritional and pharmacological consequences. Aims To assess the prevalence, causes and symptoms of complications after obesity surgery, to elucidate and compare therapy recommendations for macro‐ and micronutrient deficiencies, and to explore surgically‐induced effects on drug absorption and bioavailability, discussing ramifications for long‐term therapy and prophylaxis. Methods PubMed, Embase and MEDLINE were searched using terms including, but not limited to, bariatric surgery, gastric bypass, obesity surgery and Roux‐en‐Y, coupled with secondary search terms, e.g. anaemia, micronutrients, vitamin deficiency, bacterial overgrowth, drug absorption, pharmacokinetics, undernutrition. All studies in English, French or German published January 1980 through March 2014 were included. Results Macro‐ and micronutrient deficiencies are common after obesity surgery. The most critical, depending on surgical technique, are hypoalbuminemia (3–18%) and deficiencies of vitamins B1 (≤49%), B12 (19–35%) and D (25–73%), iron (17–45%) and zinc (12–91%). Many drugs commonly administered to obese patients (e.g. anti‐depressants, anti‐microbials, metformin) are subject to post‐operative and/or PPI‐associated changes affecting bioavailability and absorption. Conclusions Complications are associated with pre‐operative and/or post‐operative malnutrition or procedure‐related changes in intake, absorption and drug bioavailability. The high prevalence of nutrient deficiencies after obesity surgery makes life‐long nutritional monitoring and supplementation essential. Post‐operative changes to drug absorption and bioavailability in bariatric patients cast doubt on the validity of standard drug dosage and administration recommendations.